Magnetostriction of Tb-Fe-(B) thin films fabricated by RF magnetron sputtering - Lim, SH; Choi, YS; Han, SH; Kim, HJ; Shima, T; Fujimori, H (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 1997)
The magnetostriction of TbFe and TbFeB thin films is systematically investigated over a wide composition range from 40.2 to 68.1 at.% Tb for the B-free alloys and from 44.1 to 66.6 at.% Tb for the B containing thin films. The films were fabricated by rf magnetron sputtering. The microstructure mainly consists of an amorphous phase at low Tb contents and, at high Tb contents, a mixture of an amorphous phase and an alpha Tb phase. Excellent magnetostrictive characteristics, particularly at low magnetic fields, are achieved in both TbFe and TbFeB thin films; for example, a magnetostriction of 138 ppm is obtained in a TbFeB thin film at a magnetic field as low as 30 Oe. These excellent magnetostrictive properties of the present thin films are supported by the excellent magnetic softness, the coercivity below 10 Oe and a typical squared-loop shape with the saturation field as low as I kOe. It is considered that, due to the excellent low field magnetostrictive characteristics, the present TbFe based magnetostrictive thin films are suitable for Si based microdevices.
Keywords: TB-FE FILMS; DEPENDENCE